Characterization of mesenchymal stem cells in pre-B acute lymphoblastic leukemia - Hughes, Anastasia M.; Kuek, Vincent; Oommen, Joyce; Chua, Grace-Alyssa; van Loenhout, Maria; Malinge, Sebastien; Kotecha, Rishi S.; Cheung, Laurence C. (Frontiers in Cell and Developmental Biology, 2023)
Components of the bone marrow microenvironment (BMM) have been shown to mediate the way in which leukemia develops, progresses and responds to treatment. Increasing evidence shows that leukemic cells hijack the BMM, altering its functioning and establishing leukemia-supportive interactions with stromal and immune cells. While previous work has highlighted functional defects in the mesenchymal stem cell (MSC) population from the BMM of acute leukemias, thorough characterization and molecular profiling of MSCs in pre-B cell acute lymphoblastic leukemia (B-ALL), the most common cancer in children, has not been conducted. Here, we investigated the cellular and transcriptome profiles of MSCs isolated from the BMM of an immunocompetent BCR-ABL1+ model of B-ALL. Leukemia-associated MSCs exhibited reduced self-renewal capacity in vitro and significant changes in numerous molecular signatures, including upregulation of inflammatory signaling pathways. Additionally, we found downregulation of genes involved in extracellular matrix organization and osteoblastogenesis in leukemia-associated MSCs. This study provides cellular and molecular insights into the role of MSCs during B-ALL progression.